Mechanochemical-treated Cr-promoted vanadyl pyrophosphate catalyst for n-butane oxidation to maleic anhydride - Yap, Taufiq Yun Hin; Yeoh, M. M. (Taylor & Francis, 2008)
Cr-promoted vanadium phosphate (VPO) catalyst was synthesized by mechanotreating VOHPO4·0.5H2O in cyclohexane for 2 hr using a high energy planetary ball miller followed by calcination in a flow of n-butane/air mixture at 673 K. The physico-chemical properties of the sample were investigated by several characterization techniques such as BET, XRD, redox titration, SEM, and TPR. The data were compared to the unmilled material. BET surface area measurement of the milled catalyst showed that it possesses higher surface area (13.2 m2 g−1) compared to the unmilled catalyst (6.4 m2 g−1). Milling also caused a slight increment in the average oxidation state of vanadium as well as the percentage of V5+ oxidation state. XRD pattern of the milled material revealed that the major diffraction peaks were broadened thus indicating a reduction of particle size. SEM micrographs showed the lost in the blossom morphology and the formation of layer packages, with more circular particles in the milled catalyst. The amount of active lattice oxygen species being removed from V4+-O− pairs increased significantly for mechanochemical treated Cr-doped VPO catalyst leads to the enhancement of the catalytic activity for n-butane oxidation to maleic anhydride.